Economic Impact of International Remittances on Consumption in Pakistan - Nisar Ahmad, Ph.D,Zakir Hussain, Ph.D (JSSH, 2023)
Pakistan received a greater share in remittances from oil rich Gulf-region and the United State of America. The huge amount of remittances in Pakistan especially towards the rural areas of the country provided support to remove the financial constraints of the receiving households. In the present study, the impact of international remittances on consumption at aggregate level in Pakistan was estimated. Time series data was used to determine the impact of remittances on consumption in Pakistan. The data were taken from the Federal Bureau of Statistics, Islamabad and State Bank of Pakistan, Karachi. Augmented Dickey Fuller (ADF) unit root test was used to determine the order of integration of time series data. All the series used in the study were found integrated of order one i.e. I (1). Under these conditions, Johansen (1988) and Johansen and Juselius (1990) maximum likelihood estimation approach was used to test the co integration among the stated variables and all variables were found to be co integrated.